2022
DOI: 10.22452/mjes.vol59no1.2
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Using Ride-Hailing Service: Evidence from Malaysia

Abstract: With the entrance of Uber into the land transportation industry, ride-hailing service has gained popularity and changed the way people travel in urban areas in Malaysia. Despite the growing popularity of this new mode of cab service, studies about factors influencing consumers’ choice to use ride-hailing service are limited in developing countries. This study used primary data collected via a survey in Penang, Malaysia. This study aims to examine the factors affecting consumers’ decision to utilise ride-hailin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…For instance, 78.3% of the respondents hold a degree or higher in education, and 82.7% fall within the age range of 18 to 56. Previous research has indicated that individuals with a college degree and below the age of 56 exhibit higher rates of adoption for new ride-hailing services compared with those without a degree and over the age of 56 ( 139 , 140 ). Thus, this study contributes to our understanding of whether the general population of ride-hailing users finds the autonomous shuttle service acceptable.…”
Section: Resultsmentioning
confidence: 99%
“…For instance, 78.3% of the respondents hold a degree or higher in education, and 82.7% fall within the age range of 18 to 56. Previous research has indicated that individuals with a college degree and below the age of 56 exhibit higher rates of adoption for new ride-hailing services compared with those without a degree and over the age of 56 ( 139 , 140 ). Thus, this study contributes to our understanding of whether the general population of ride-hailing users finds the autonomous shuttle service acceptable.…”
Section: Resultsmentioning
confidence: 99%
“…Their findings showed a correlation between perceived usefulness and user pleasure that was positive. Lim et al (2018) found an important relationship of PU, subjective norms, perceived risk and perceived playfulness with the consumers' adoption of ridehailing applications in the context of Malaysia. Table 4 presents a summary of existing studies in the area of transport applications.…”
Section: Related Workmentioning
confidence: 90%
“…The acceptance of transport applications is studied in diverse geographical regions, including China (H. Li & Liu, 2014;Park & Kim, 2014;Y. Wang et al, 2018;Zhou, 2012), Brazil (Joia & Altieri, 2017), Malaysia (Lim et al, 2018;Ubaidillah et al, 2019;Weng et al, 2017), France and Switzerland (Madigan et al, 2016), Vietnam (Giang et al, 2017), Thailand (Ruangkanjanases & Techapoolphol, 2018), Indonesia (Gumilar et al, 2019), India (Ardra & Rejikumar, 2017), and Taiwan (Cheng & Huang, 2013). These studies have measured the acceptance of transport applications by utilizing and extending different models according to context and domain as presented in Table 2.…”
Section: Related Workmentioning
confidence: 99%
“…Thus, the ride-hailing business is legitimized by responding to these actors' expectations [see also the study by Anning-Dorson (2021) and Farrukh et al (2021)]. Also, by bringing institutional theory to market research, we look beyond the traditional stimulus-response approach that focuses on dyadic relationships, such as those between policymakers and ride-hailing platforms (Zhong et al, 2022) or digital platforms and passengers (Bai et al, 2019;Lim et al, 2018), to a network of actors who co-influence the institutions.…”
Section: Discussion and Theoretical Contributionmentioning
confidence: 99%
“…, 2022) or digital platforms and passengers (Bai et al. , 2019; Lim et al. , 2018), to a network of actors who co-influence the institutions.…”
Section: Discussion and Theoretical Contributionmentioning
confidence: 99%